Coinfection with dengue and hepatitis A complicated with infective endocarditis in a Yemeni patient: a case report - Alemad, Shafiq A.; Halboup, Abdulsalam M.; Aladeeb, Khaled; Al-Saleh, Mohamed; Al-Kufiley, Nuha (Springer Nature, 2021)
Introduction Coinfection with dengue and hepatitis A is rare and challenging for physicians since their clinical features can be overlapping. These infections are self-limiting but can become complicated by subsequent infective endocarditis. We report a case of infective endocarditis following a coinfection with dengue and hepatitis A. Case presentation A 17-year-old Yemeni male patient was admitted to the hospital complaining of yellowish discoloration of the skin and sclera associated with dark urine and a diffuse skin rash on the trunk and upper limbs followed by intermittent high-grade fever. Coinfection was confirmed by hepatitis A immunoglobulin M and dengue immunoglobulin M. At the time of diagnosis, white blood cells were normal, with mild neutrophilia and thrombocytopenia along with elevated C-reactive protein. Five days later, the patient was readmitted to the emergency department, complaining of high-grade fever, fatigue, myalgia, nausea, and vomiting. A systolic heart murmur was heard, and infective endocarditis was confirmed by the visualization of two vegetations on the mitral valve and coagulase-negative staphylococci after blood culture. Supportive therapies were initiated for hepatitis A and dengue fever, whereas infective endocarditis was treated with antibiotics for 4 weeks. The patient recovered completely from dengue, hepatitis A, and infective endocarditis. Conclusion In endemic areas, it is reasonable to screen for coinfection with dengue and hepatitis A since they are superimposed on each other. Subacute infective endocarditis may occur following initial dengue and hepatitis A coinfection, especially among patients with rheumatic heart disease. An echocardiogram is a pivotal workup for evaluating a patient with persistent fever of unknown origin.